2004
DOI: 10.1007/s10708-005-1929-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilisation of health services by women in rural and urban areas in Ghana

Abstract: The paper examines the factors that influence the utilisation of health services by women in the rural and urban areas in Ghana. The systematic sampling procedure was used to draw the sample from women aged 18 and above with diverse backgrounds from Ahafo-Ano South district, representing the rural districts and Kumasi metropolis, representing the urban districts. The research instruments used for data collection were the questionnaire and formal interviews. Multiple regression was the main tool for analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…Addai [29] also noted that, compared to the Northern parts of Ghana, women residing in rural areas of western and central regions were two times more likely to see a physician for prenatal care compared with women in the Northern part. This is largely attributable to the adequacy and ease of access to health personnel and facilities among women living in rural areas of the southern parts of the country compared to those in the Northern part of the country [29][30][31][32]. Our study contributes to the body of knowledge available on skilled delivery by examining the determinants of skilled delivery in the Northern part of Ghana and making useful recommendations for policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Addai [29] also noted that, compared to the Northern parts of Ghana, women residing in rural areas of western and central regions were two times more likely to see a physician for prenatal care compared with women in the Northern part. This is largely attributable to the adequacy and ease of access to health personnel and facilities among women living in rural areas of the southern parts of the country compared to those in the Northern part of the country [29][30][31][32]. Our study contributes to the body of knowledge available on skilled delivery by examining the determinants of skilled delivery in the Northern part of Ghana and making useful recommendations for policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our objective in this paper is to investigate the factors that affect the choice of PPP, and their direction of association and magnitude with the choice of PPP. Indeed, some studies on patient hospital (provider) choice and/or utilisation of healthcare services have been conducted in developing countries [16][17][18][19][20] and developed countries. 1,6,8,9,[21][22][23][24] However, most of these studies, eg, Dzator and Asafu-Adjaye, 17 examined patient hospital choice under conditions where price (user fees) existed and/ or for a particular disease.…”
mentioning
confidence: 99%
“…Previous study with different viewpoints from the present study stated that the principle factor that mostly affects vulnerable groups was lack of financial capacity to utilize health services and a lack of need to use health facilities [28,30]. A variety of factors have been acknowledged in other previous studies as the leading causes of poor utilization of any Primary Health Care Services, regardless of them being free services [31][32][33] : these include poor socio-economic status, lack of physical accessibility, cultural beliefs and perceptions, low literacy level of mothers and large family size [3,16,33].…”
Section: Yes or Nomentioning
confidence: 54%
“…A study by Harris and others reported that the average travelling time to health facilities in the rural areas in South Africa was about 30 -40 minutes and some would need to travel the whole day [26]. Extensive travelling time has a negative impact and demotivates communities in accessing healthcare facilities as they might not be physically well enough to walk [27,28].…”
Section: Travelling Timementioning
confidence: 99%